On the island - Garvis Graves, Tracey (Plume book., 2011)
Stranded on an uninhabited island after their private plane crashes, thirty-year-old Anna Emerson and sixteen-year-old T.J. Callahan, her tutee, struggle to survive and, as the months pass, slowly fall in love.